A experiência do povo Mura do Careiro da Várzea com o turismo: entrelaçamentos entre a defesa do território, alternativas de renda e identidade - Andrade, Andreia Benchimol de (2022)
The tourism on indigenous lands (ILs) is an activity that began illegally, and and was regulated by FUNAI through Normative Instruction 03/2015. The regularization of the activity aroused the insterest of many indigenous people in developing ethnotourism or ecotourism as an alternative of territorial and environmental management, in addition to a possible generation of income. The people from Careiro da Varzea, in turn, in 2015, had the initiative to develop in ecotourism Project for their territory. Therefore, the research had as object of to study the “Jabuti Community Ecotourism Project” created by the Mura do Careiro da Varzea Indigenous Leadership Organization (OLIMCV), with the general objective of analyzing the mobilization of the Mura People, through the OLIMCVOrganization of Indigenous Leaders Mura from Careiro da Varzea, to protect the territory, projects and income alternatives in the management of the territory. The methodology used to carry out the research had as method of analysis the Latour’s Network Actor Theory (2012). Two stages were used for data collection, the first was the bibliographic and documentary research through access to files made available by OLIMCV, such as the association’s statute, protocol Trincheiras Yandé Peara Mura. And the second stage consisted of field research, carried out by two different instruments: the workshop on IN 03/2015 as a FUNAI guideline for the construction of the visitation plan, carried out by NEICAM/UEA in October 2021, and the virtual interviews held by the Google Meet platform in January/2022. The main results are that currently the Mura people face several territorial and social conflicts with non-indigenous people, including deforestation within the territory, illegal tourism and sport fishing, the attempt to legalize mining activity by the company Potassio do Brasil, harassment by farmers, among others. These factors justified the interest of the Mura people in creating the Ecotourism Jabuti project with the central objective of mitigating deforestation within the territory, in addition to providing an economic alternative by structuring a physical base that would not only serve to welcome tourists but also function as an office for the OLIMCV.